An Experimental Study on Enhancing Progressive Collapse Resistance Using a Steel Fiber-Reinforced Concrete Frame - Alshaikh, Ibrahim M. H.; Abu Bakar, B. H.; Alwesabi, Emad A. H.; Abadel, Aref A.; Alghamdi, Hussam; Wasim, Muhammad (American Society of Civil Engineers, 2022)
This paper aims to investigate the inclusion efficiency of straight microsteel fibers to improve the structural ductility and deformability of reinforced concrete frames to achieve progressive collapse resistance. Four RC frames behavior has been tested at one-third scale in the removal scenario of the middle column. To compare, two frames without steel fiber were prepared to be the control samples. Frames of 0.5% steel fiber fraction volume were also prepared. The study aims to analyze mechanical properties, crack pattern, failure mode, structural ductility, and load-displacement behavior of the frames of normal concrete (NC), together with steel fiber-reinforced concrete (SFC). Based on the findings, an enhancement was observed in the structural ductility (the increase ratio reached up to 26%), stimulated by incorporating steel fiber in the normal concrete. The frames of SFC demonstrated more deflection by 19% compared with NC frames. Steel fiber, therefore, can be utilized to enhance RC elements ductility as an innovative design strategy in inhibiting progressive collapse.